Strategi Pengembangan Pemasaran Di Kampung Wisata Rajut Binong Kota Bandung - Fajri, Khoirul; Astiana, Rachmat; Agoes, Adrian (STIEPAR YAPARI Bandung, 2024)
The context for this research is a paucity of initiatives that support tourism marketing, particularly the establishment of innovative tourist communities in Bandung. The goal of this research is to make recommendations to the Bandung City Government, specifically the Disbudpar, for creating tourism marketing strategies, particularly in the Binong Rajut Creative Village. Binong Knitting Tourism Village has significant potential as a creative tourism destination. According to the SWOT analysis, this town is in a strategic position to adopt an aggressive expansion strategy that includes leveraging its strengths in implementing Sapta Pesona, diversifying tourist packages, and providing enough amenity facilities. However, shortcomings in HR and integrated marketing competencies must be rectified. Strategy recommendations include maximizing social media advertising, enhancing the quality and quantity of tourism products, and working with the government, tourism sector stakeholders, communities, and academia to promote innovation and competitiveness. Better management can be achieved through training, seminars, and conversations that create collaborative networks and enhance HR competency. With a planned approach and stakeholder participation, the Binong Knitting Tourism Village may grow its attractiveness as a tourist attraction, benefit the local economy, and conserve local culture. Implementing this plan will promote long-term growth and community welfare in the tourism industry, establishing the Binong Rajut Tourism Village as a successful model for community-based tourism development.